'The lesser devil you don't know': a qualitative study of smokers' responses to messages communicating comparative risk of electronic and combusted cigarettes. Issue 2 (30th April 2019) - Owusu, Daniel; Lawley, Rachel; Yang, Bo; Henderson, Katherine; Bethea, Brittaney; LaRose, Christopher; Stallworth, Sam; Popova, Lucy
Abstract : Introduction: Communicating to smokers that e-cigarettes deliver lower levels of harmful chemicals than combusted cigarettes is a challenging issue. This study qualitatively explored smokers' interpretations of messages communicating the risk of e-cigarettes relative to cigarettes (comparative risk messages). Method: We developed 12 print comparative risk messages and evaluated them in 12 focus groups with 72 adult smokers (18+ years old) in Atlanta, Georgia. Results: Participants interpreted uncertainty about health effects of e-cigarettes as an indicator of significant unknown risks, which some believed to be potentially more severe than the known effects of cigarettes (such as cancer and heart disease). Also, participants were sceptical about the lower risk claims. Some participants misinterpreted what 'switching completely' or 'switching 100% of the time' means, perceiving switching from e-cigarettes to combusted cigarettes as comparable with the use of both products. When chemicals in e-cigarettes were mentioned (eg, nicotine or formaldehyde), participants viewed e-cigarettes as very harmful and had difficulty reconciling this belief with the reduced risk claim. Comparative risk messages emphasising smoking risks were perceived as effective. Participants also appreciated being given an option to switch if they cannot quit. Participants suggested the inclusion of more facts and statistics and a credible message source (eg, public health agencies) to increase message effectiveness. Conclusion: Comparative risk messages may be more acceptable to smokers if they show direct comparisons of the number of toxic chemicals in cigarettes and e-cigarettes, are attributed to a credible source(s), and emphasise smoking risks.